Migração e qualidade de vida: caso dos brasileiros na Irlanda em dois momentos 2008 e 2018 - Silva, Milena Cristina da (2019)
This dissertation aims to analyze the quality of life and work conditions of Brazilian migrants in Ireland, in two different moments, in the years 2008 and 2018. This research is necessary due to the lack of studies related to the Brazilian community in Ireland, mainly regarding their perception of their quality of life and work. There are still few theoretical studies on the quality of life and work related to the migration of Brazilians, although there is a significant number of articles and scientific research on migration and quality of life. This is a mixed, quantitative and qualitative research, carried out in two stages, in different years, with an interval of 10 years. The initial phase took place in 2008 in Ireland, which was carried out through quantitative research that used as a basis a sociodemographic questionnaire and the quality of life test called “The Quality of Life Assessment Instrument” (The World Health Organization Quality of Life (WHOQOL – bref), widely validated in different countries. The second stage was held in Brazil in 2018, using a semi-structured interview script with people who had migrated to Ireland. An important point in the results of this study for the Brazilian migrant community in Ireland was the improvement in the perception of quality of life, especially in the financial, economic and security areas. This improvement was most significant for migrants who invested in local language knowledge, ie the English language and were accompanied by their family members.